2013
DOI: 10.3346/jkms.2013.28.8.1129
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Dihydropyrimidine Dehydrogenase Genetic Variants by Direct Sequencing in Different Ethnic Groups

Abstract: Dihydropyrimidine dehydrogenase (DPYD) is an enzyme that regulates the rate-limiting step in pyrimidine metabolism, especially catabolism of fluorouracil, a chemotherapeutic agent for cancer. In order to determine the genetic distribution of DPYD, we directly sequenced 288 subjects from five ethnic groups (96 Koreans, 48 Japanese, 48 Han Chinese, 48 African Americans, and 48 European Americans). As a result, 56 polymorphisms were observed, including 6 core polymorphisms and 18 novel polymorphisms. Allele frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Different populations and races show different prevalence of IVS14 + 1G > A polymorphism in the DPYD [29]. In a study on 72 patients in Taiwan, 2.7% of patients had IVS14 + 1G > A polymorphism in the DPYD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Different populations and races show different prevalence of IVS14 + 1G > A polymorphism in the DPYD [29]. In a study on 72 patients in Taiwan, 2.7% of patients had IVS14 + 1G > A polymorphism in the DPYD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Dutch Pharmacogenetics Working Group (DPWG) guidelines define these same four variants as risk factors for FP-related toxicity and recommend reducing treatment dosage when a patient possesses one of them [47]. Although DPYD*9A, *5, and *6 are common variants in many ethnic groups, these four risk variants have not yet been identified in Asians [48][49][50].…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 99%
“…Our previous study, as well as Cho et al, reported on DPYD genetic variants in Koreans. 15,16 Sohn et al 17 also examined DPYD activity in a Korean population. To date, however, association between DPYD genetic variants and their enzyme activity in Koreans has not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, as a follow-up to our previous study, 15 we directly sequenced DPYD and determined its enzyme activity in 73 Korean subjects. Further association analysis between DPYD genetic variants and enzyme activity was also conducted based on the genotype of each genetic variant.…”
Section: Introductionmentioning
confidence: 99%